2023
DOI: 10.1002/met.2156
|View full text |Cite
|
Sign up to set email alerts
|

Influence of climatic conditions on Normalized Difference Vegetation Index variability in forest in Poland (2002–2021)

Kinga Kulesza,
Agata Hościło

Abstract: The influence of climate change on forest condition is noticeable. Forest ecosystem stress caused by climate change has already been manifested in several parts of Europe, including Poland. Thus, the main objective of this paper is to investigate for the entire area of Poland a long‐term trend and variability of forest greenness expressed as the Normalized Difference Vegetation Index (NDVI), derived from two decades (2002–2021) of remote sensing Moderate Resolution Imaging Spectroradiometer (MODIS) data. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 62 publications
1
5
0
Order By: Relevance
“…This finding resonates with the wider body of research that underscores the importance of meteorological elements in vegetative trends [66]. For instance, Kulesza and Hościło [67] have concluded that rainfall is the most significant natural factor influencing forest health across Poland. Moreover, Pravalie et al [68] found that in mountain regions such as the Carpathians, the greening trend is more closely associated with temperature increases, while in our study area, precipitation has a more pronounced effect.…”
Section: Driving Factors Of Vegetation Change In High and Low-intensi...supporting
confidence: 58%
“…This finding resonates with the wider body of research that underscores the importance of meteorological elements in vegetative trends [66]. For instance, Kulesza and Hościło [67] have concluded that rainfall is the most significant natural factor influencing forest health across Poland. Moreover, Pravalie et al [68] found that in mountain regions such as the Carpathians, the greening trend is more closely associated with temperature increases, while in our study area, precipitation has a more pronounced effect.…”
Section: Driving Factors Of Vegetation Change In High and Low-intensi...supporting
confidence: 58%
“…In the last two decades a slightly positive trend in condition of the forests in Poland was noticed, with a mean NDVI increase of 0.088×10 -3 per year (2002-2021) (Kulesza and Hościło, 2023). The biggest increase of mean annual NDVI (by 0.030 in 20 years) was observed in central-eastern Poland, while it was weaker in southern, western and northern edges of the study area.…”
Section: Basic Characteristics Of VI and Meteorological Elementsmentioning
confidence: 81%
“…The trend of mean annual T was positive over the entire research area, resulting in the increase in T by 1 to 1.6°C (in southern and eastern regions) (2002-2021) (Kulesza and Hościło, 2023). In central and eastern regions the statistically significant increase in ETo was also reported, with a mean increase of 1.79 mm per year (while mean annual ETo is ca.…”
Section: Basic Characteristics Of VI and Meteorological Elementsmentioning
confidence: 84%
See 1 more Smart Citation
“…Several trend studies did not include a precise description of the effects at the forest level (phenological changes, mortality, or productivity changes). However, these studies commonly described changes in vegetation indices and associated changes in vegetation as a result of changing climatic conditions [101,109,110,[206][207][208][209][210][211][212][213][214].…”
Section: Trend Changementioning
confidence: 99%